2007
DOI: 10.1093/cercor/bhm064
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Signals Related to Choices and Outcomes in the Dorsolateral Prefrontal Cortex

Abstract: Although economic theories based on utility maximization account for a range of choice behaviors, utilities must be estimated through experience. Dynamics of this learning process may account for certain discrepancies between the predictions of economic theories and real choice behaviors of humans and other animals. To understand the neural mechanisms responsible for such adaptive decision making, we trained rhesus monkeys to play a simulated matching pennies game. Small but systematic deviations of the animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
126
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(139 citation statements)
references
References 27 publications
12
126
0
1
Order By: Relevance
“…Overall, apparently in line with previous studies having demonstrated an implication of the dlPFC in the visuo-spatial working memory (e.g., Courtney et al, 1998;Funahashi et al, 1993;Smith and Jonides, 1999;Qi et al, 2010;Wilson et al, 1993), the present results show changes resulting from right dlPFC lesion, mainly on parameters reflecting a processing of either static or rotation-moving visuo-spatial information, in relation to prehension movements and the planning of the optimal picking sequence to perform manual prehension tasks, of which execution depends on dlPFC (e.g., Amiez and Petrides, 2007;Barraclough et al, 2004;Fletcher et al, 1997;Goel and Dolan, 2000;Goldberg et al, 1994;Heekeren et al, 2006;Seo et al, 2007). Furthermore, the present results are consistent with the model of Petrides suggesting that dlPFC is involved in high order executive control functions, as well as with a model proposing a hemispheric laterality effect, with a greater right PFC activation during spatial tasks (Baker et al, 1996;McCarthy et al, 1996;Reuter-Lorenz et al, 2000).…”
Section: Discussionmentioning
confidence: 54%
“…Overall, apparently in line with previous studies having demonstrated an implication of the dlPFC in the visuo-spatial working memory (e.g., Courtney et al, 1998;Funahashi et al, 1993;Smith and Jonides, 1999;Qi et al, 2010;Wilson et al, 1993), the present results show changes resulting from right dlPFC lesion, mainly on parameters reflecting a processing of either static or rotation-moving visuo-spatial information, in relation to prehension movements and the planning of the optimal picking sequence to perform manual prehension tasks, of which execution depends on dlPFC (e.g., Amiez and Petrides, 2007;Barraclough et al, 2004;Fletcher et al, 1997;Goel and Dolan, 2000;Goldberg et al, 1994;Heekeren et al, 2006;Seo et al, 2007). Furthermore, the present results are consistent with the model of Petrides suggesting that dlPFC is involved in high order executive control functions, as well as with a model proposing a hemispheric laterality effect, with a greater right PFC activation during spatial tasks (Baker et al, 1996;McCarthy et al, 1996;Reuter-Lorenz et al, 2000).…”
Section: Discussionmentioning
confidence: 54%
“…This area is known to carry out a variety of cognitive functions including the top-down modulation of posterior brain regions (Miller, 2000;Miller and Cohen, 2001), maintenance of information in working memory (Levy and Goldman-Rakic, 2000;Curtis and D'Esposito, 2004), and manipulation of information in working memory (Petrides, 2000). Several studies have also shown that the activity of some parts of DLPFC is correlated with various measures of value during perceptual and economic decision-making tasks (Kim and Shadlen, 1999;Wallis and Miller, 2003;Seo et al, 2007). The results in this paper suggest that DLPFC plays a role in the computation of goal values in both appetitive and aversive domains, perhaps by supplying inputs to OFC.…”
Section: Discussionmentioning
confidence: 99%
“…However, reasonable candidates include dopaminergic (DA) neurons in the ventral tegemental area (VTA) and the substantia nigra pars compacta (SNc) that might influence activity in visual cortex via direct projections to early areas of visual cortex (Berger et al 1988(Berger et al , 1991Devoto and Flore 2006). However, these projections are generally thought to be sparse, so it is likely that indirect DA signals relayed through the striatum and then to frontal and parietal cortex play an important role in regulating value-related changes in early visual cortex (Barraclough et al 2004;Ding and Hikosaka 2006;Dorris and Glimcher 2004;GlĂ€scher et al 2009;Glimcher 2003;Hikosaka et al 2008;Hollerman and Schultz 1998;Ikeda and Hikosaka 2003;Lau and Glimcher 2007;Leon and Shadlen 1999;Luk and Wallis 2009;Platt and Glimcher 1999;Schultz and Dickinson 2000;Seo et al 2007;Sugrue et al 2004;Wallis and Miller 2003;Watanabe 1996). Indeed, many of the cortical targets of reward signals-such as oculomotor neurons in frontal and parietal cortex-are ideally situated to send modulatory feedback signals to earlier sensory areas so that the cortical representation of high-value stimulus features can be enhanced (Bisley and Goldberg 2003;Ding and Hikosaka 2006;Gold and Shadlen 2007;Serences and Yantis 2006;Shadlen and Newsome 2001).…”
Section: Value and Population Responses In Human Visual Cortexmentioning
confidence: 99%